Accelerated Aging Test in Thyme Seeds (Thymus vulgaris L.) - Lourenço, Flávia Mendes dos Santos; Sá, Marco Eustáquio de; Yamashita, Oscar Mitsuo; Silva, Vinícius Martins; Martins, Juliana Trindade; Oliveira, Jéssica Alves de; Cotrim, Mayara Favero; Silva, Renan Furquim da; David, Grace Queiroz; Peres, Walmor Moya (Journal of Agricultural Studies, 2021)
Evaluating seed quality with precision and accuracy is one of the priorities for obtaining high quality material. This study aimed to evaluate whether the variations in the performance of the accelerated aging test, in terms of exposure time and temperature, in the traditional form or in saline solution, would result in an efficient combination to evaluate the physiological quality of thyme seeds (Thymus vulgaris L.). The seeds were submitted to the tests of total germination, germination speed index, first germination count, seedlings emergence, seedling length, seedling dry mass, cold test, electrical conductivity, variations in the conduction of the accelerated aging test and the water content of the seeds was performed after each accelerated aging period. The treatments were the combination of temperatures (36, 38, 40 and 42 ºC), exposure time (24, 36, 48 and 72 hours) and two procedures (traditional and saline), with four replications for each batch. Traditional accelerated aging test at 42 ºC and 24 hours of exposure time, and saline solution accelerated aging test at 38 ºC and 24 hours of exposure time showed sensibility to evaluate physiological potential for thyme seed. For both saline solution and traditional accelerated aging test, the exposition time of 24 hours was efficient to evaluate physiological potential of thyme seeds.